2020
DOI: 10.18632/aging.103305
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of autophagic flux induced by Abeta in the brain of postmortem Alzheimer’s disease patients, animal models and cell models

Abstract: Autophagy has been reported to play a dual "double-edged sword" role in the occurrence and development of Alzheimer's disease (AD). To assess the relationship between AD and autophagy, the dynamic changes of autophagic flux in the brain of postmortem AD patients, animal models and cell models were studied. The results showed that autophagosomes (APs) accumulation and expression of lysosomal markers were decreased in the brains of AD patients. In the brain of APP/PS1 double transgenic mice, APs did not accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Autophagy dysregulation has been reported in AD brain, which contributes to the formation of AD pathologies [ 31 ]. Therefore, we investigated the involvement of autophagy in the accumulation of Aβ plaques and NP tau pathology in APP/PS1 mice.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy dysregulation has been reported in AD brain, which contributes to the formation of AD pathologies [ 31 ]. Therefore, we investigated the involvement of autophagy in the accumulation of Aβ plaques and NP tau pathology in APP/PS1 mice.…”
Section: Resultsmentioning
confidence: 99%
“…Our results were consistent with reports by Zhao et al that decreased levels of autophagic‐related genes and autophagic flux were examined in 9‐month‐old and 12‐month‐old transgenic AD mice (Manczak et al, 2018; Zhao et al, 2020). However, it is controversial because some studies indicate an increased autophagic level in 4‐ to 6‐month‐old AD mice (Long et al, 2020; Sanchez‐Varo et al, 2012). The differences of these observations might be attributed to the age‐dependent down‐regulated expression of autophagy‐related genes following the pathology progression in AD (Omata et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that AD pathogenesis is accompanied by autophagic disorder (Peric and Annaert, 2015 ; Zhang et al, 2016 ), which may occur in different stages of autophagic flux. In our previous study, we explored the function of autophagic flux in AD (Long et al, 2020 ). Immunofluorescence staining showed that autophagosomes accumulated in the brain tissues of AD patients, and the lysosomal marker Lamp1 was decreased.…”
Section: Discussionmentioning
confidence: 99%